Swallowing Problems after Thyroidectomy - Elbeltagy,Yasser Mohammed (2022)
Abstract Introduction Thyroidectomy is a common procedure. Certain swallowing problems could happen after this surgery and affect the quality of life of the patient. Objective To evaluate swallowing after thyroidectomy in the early and late postoperative periods and to correlate subjective and objective parameters. Methods A prospective study with100 patients who underwent total thyroidectomy at our institution from April 2018 to September 2019. Each patient was assessed by the Arabic version of the Eating Assessment Tool (EAT-10) questionnaire and the fiberoptic endoscopic evaluation of swallowing (FEES) preoperatively, and in the early postoperative (EPO) and late postoperative (LPO) periods. Results The rate of dysphagia was of 82% in the EPO period, and of 36% in the LPO period. Two groups were compared regarding vocal fold mobility using the FEES. Group I included 89 patients with normal vocal fold mobility, 42% of whom had early dysphagia, and only 22% had late dysphagia. Regarding swallowing, we found that in the EPO period, the rates of delayed triggering, aspiration, penetration and residue were of 12.4%, 0%, 0%, and 42.7% respectively. Group II (unilateral immobile vocal fold) included 11 patients in the EPO evaluation, and all of them had early dysphagia. Conclusion Swallowing problems can occur in patients after thyroidectomy regardless of alterations in larynx mobility, and they are characterized by delayed triggering and stasis of food, which are also noticed in the LPO period, though more frequently in the EPO period. Moreover, there is a highly significant correlation between the subjective and objective parameters of swallowing in both EPO and LPO periods.